IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU - Febri Yuliani, Riski Yanto, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of Pekanbaru Mayor Regulation. This study aims to find out and analyze the implementation and factors that influence the Implementation of the Regulation of the Mayor of Pekanbaru. This type of research is a qualitative research method approach. Primary data collection through interviews with research informants is the Assistant Head of Organization and Secretary of the City Government. The results of the study show that it is necessary to amend the Regulation of the Mayor